2020
DOI: 10.1111/codi.15382
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of faecal incontinence with autologous expanded mesenchymal stem cells: results of a pilot study

Abstract: Aim Management of faecal incontinence (FI) remains challenging because no definitive optimal treatment for this condition has yet been determined. Regenerative medicine could be an attractive therapeutic alternative for treating FI. Here, we aimed to determine the safety and feasibility of autologous expanded mesenchymal stem cells derived from adipose tissue (AdMSCs) in the treatment of patients diagnosed with structural FI. Method This was a randomized, multicentre, triple‐blinded, placebo‐controlled pilot s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…We would like to thank Balaphas et al for the interest shown in our article [1]. Many of the observations they make in their kind letter have already been discussed in our paper and therefore we are in agreement with them.…”
supporting
confidence: 89%
“…We would like to thank Balaphas et al for the interest shown in our article [1]. Many of the observations they make in their kind letter have already been discussed in our paper and therefore we are in agreement with them.…”
supporting
confidence: 89%
“…Recent modifications of this technique by using elastic bands in adults with fecal incontinence has shown promising results [18] . Other new techniques like autologous expanded mesenchymal stem cells infusions still lack demonstrated efficacy [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 11 studies met the inclusion criteria and were incorporated into the final assessment [16][17][18][19][20][21][22][23][24][25][26]. Specifically, we found 7 papers dealing with stem cell therapy for stress urinary incontinence [16][17][18][19][20][21][22] and 4 with anal incontinence [23][24][25][26]. No papers concerning the use of SC for prolapse repair were retrieved.…”
Section: Study Assessmentmentioning
confidence: 99%
“…In evaluating the impact of stem cell therapy on anal incontinence, 4 studies were analyzed (Table 2) [23][24][25][26]. Studies' design included two prospective single-arm studies [24,25] and two randomized controlled trials [23,26]. In total, 66 patients underwent stem cell therapy in the considered studies, including 10 men.…”
Section: Stem Cell Therapy For Anal Incontinencementioning
confidence: 99%